Psychometric evaluation of a novel measure of trauma-related cannabis use to cope - Sage E. Hawn; Terrell A. Hicks; Christopher Latourrette; Anita Thomas; Daniela Chaname; Sarah Ehlke; Abigail Powers Lott (European Journal of Psychotraumatology)
Background: Posttraumatic stress disorder (PTSD) and cannabis use disorder (CUD) are commonly comorbid and are associated with many negative public health outcomes. One plausible explanation for this comorbidity comes from a self-medication framework, which suggests people use cannabis to cope with PTSD symptoms. Despite theoretical and empirical evidence for PTSD-related cannabis use to cope, no measure of this construct exists.Objective: We sought to address this gap by developing and validating a novel measure of PTSD-specific cannabis self-medication, which we have termed the Trauma-Related Cannabis Use to Cope (TRCU) questionnaire.Method: The psychometric properties of the TRCU and how it relates to relevant constructs were examined among a diverse sample of 345 trauma-exposed undergraduate cannabis users (Mage = 22.19, SD = 6.45; 46.7% White; 79.7% woman-identifying) using structural equation modelling in Mplus.Results: Study findings indicate that the TRCU is a more precise and targeted measure of cannabis use to cope with PTSD symptomology, as compared to existing measures of cannabis coping motives. Furthermore, our data support the use of the TRCU as a four-factor scale, assessing cannabis use to cope with the four DSM-5 PTSD symptom clusters (χ2(164) = 257.83, p < .001; CFI = .969; TLI = .965; RMSEA = .041). We also found strong evidence supporting the construct and criterion validity of the TRCU, specifically in relation to PTSD symptoms, cannabis use, and cannabis-related issues and dependence.Conclusions: Results support the use of the TRCU in future self-medication research and as a clinically useful screening tool for identifying individuals with PTSD who are at risk for developing CUD.